A STUDY ON THE EFFICACY OF PATOLADI KASHAYA AND KARANJADI LEPA IN VICHARCHIKA W.S.R. TO ECZEMA (AYUSHDHARA, 2016)
Background: Eczema is most common chronic relapsing skin disease seen in infancy and childhood. It is slightly more common in boys than girls. According to Ayurveda, Vicharchika is a major problem in skin diseases. Despite of great advance in dermatology and the advent of powerful antibiotics, antifungal as well as steroids, Eczema continues to defy the best effect of dermatologists. These modern medicines also have serious side effects like liver and kidney failure, bone marrow depletion etc. Long term use of tropical steroids may result in skin atrophy, stria, and telangiectasia. Hence it is the need of the hour to find out safe and effective medicine for Vicharchika and here comes the role of Ayurveda. The special treatment therapy of Ayurveda provides long lasting results by treating the disease and preventing reoccurrence. Finally gives a better quality of life. In Ayurveda, Shodhana, Shamana and Nidana parivarjana are the principle treatment for any disease. Shaman chikitsa is more preferable than Shodhana chikitsa in pediatrics age group, because children’s have mridu and sukumar body constitution. The selected drug compounds, i.e. Patoladi kashaya and Karanjadi lepa are well indicated for Kushta and both act as Shaman dravyas in Kustha. Aims and objectives: To study the efficacy of Patoladi kashaya, Karanjadi lepa and Placebo in Vicharchika. To find out economical therapy for Vicharchika with minimum or no side effects. Material and methods: Total 60 patients having signs and symptoms of Vicharchika were selected randomly from OPD and IPD of Kaumarbhritya, S. V. Ayurvedic hospital, Tirupati and enrolled equally in two groups (n=30). Patients of Group A were administered with Patoladi Kashaya and Karanjadi lepa (according to age), Group B were with Placebo Kashaya and Lepa for 1 month. Patients were assessed at 15th day, 30th day, 45th day and 60th day. ANOVA test was applied for significance. Results: Group A shows better result than Group B in both subjective and objective parameters especially in Kandu, Rukshata, Vaivarnya and Pidika. Conclusion: Patoladi kashaya orally and Karanjadi Lepa externally is very effective management of Vicharchika.